Principles of accounting 3rd edition - Nik Ibrahim, Nik Haslina; Mazali, Manizah; Abdul Rahman, Noredah; Mohd Noor, Rohana; Hussain, Husnamaria; Ngadimun, Sih Sayekti (Cengage Learning Asia Ltd, 2022)
The 3rd edition was written was written to improve the previous editions and to add new chapters that are relevant for foundation students.